Stimulus-Specific Expression, Selective Generation and Novel Function of Grass Carp (Ctenopharyngodon idella) IL-12 Isoforms: New Insights Into the Heterodimeric Cytokines in Teleosts - Qiu, Xingyang; Sun, Hao; Wang, Dan; Ren, Jingqi; Wang, Xinyan; Zhang, Anying; Yang, Kun; Zhou, Hong (Frontiers in Immunology, 2021)
Interleukin-12 (IL-12) is a heterodimeric cytokine composed of a p35 subunit specific to IL-12 and a p40 subunit shared with IL-23. In this study, we unveiled the existence of two p35 paralogues in grass carp (named gcp35a and gcp35b). Notably, gcp35a and gcp35b displayed distinct inducible expression patterns, as poly I:C merely induced the gene expression of gcp35a but not gcp35b, while recombinant grass carp interferon-gammargcIfn-only enhanced the transcription of gcp35b but not gcp35a. Moreover, the signaling mechanisms responsible for the inducible expression of gcp35a and gcp35b mRNA were elucidated. Because of the existence of three grass carp p40 genes (gcp40a, gcp40b and gcp40c) and two p35 paralogues, six gcIl-12 isoforms were predicted by 3D modeling. Results showed that gcp40a and gcp40b but not gcp40c had the potential for forming heterodimers with both gcp35 paralogues via the disulfide bonds. Non-reducing electrophoresis experiments further disclosed that only gcp40b but not gcp40a or gcp40c could form heterodimers with gcp35 to produce secretory heterodimeric gcp35a/gcp40b (gcIl-12AB) and gcp35b/gcp40b (gcIl-12BB), which prompted us to prepare their recombinant proteins. These two recombinant proteins exhibited their extensive regulation on Ifn-γ production in various immune cells. Intriguingly, both gcIl-12 isoforms significantly enhanced the transcription of il-17a/f1 and il-22 in lymphocytes, and their regulation on il-17a/f1 expression was mediated by Stat3/Rorγt signaling, supporting the potential of gcIl-12 isoforms for inducing Th17-like responses. Additionally, stimulatory effects of gcIl-12 isoforms on il-17a/f1 and ifn-γ expression were attenuated by gcTgf-β1 via suppressing the activation of Stat3 signaling, implying that their signaling could be manipulated. In brief, our works provide new insights into the inducible expression pattern, heterodimeric generation and functional novelty of Il-12 isoforms in teleosts.